The Effect of GEMAS-Based Learning on Junior High School Students’ Mathematical Problem-Solving Skills Based on Krulik and Rudnick’s Indicators - Ana Setiani; Hamidah Suryani Lukman; Ida Rahmawati; Novi Andri Nurcahyono (Pendidikan Matematika UNIMOR, 2026)
The PISA 2022 results indicate that Indonesian students’ mathematical performance remains below the OECD average, which calls for instructional innovations that support mathematical problem-solving at the junior high school level. This study examined the use of the Mathematics Educational Game (GEMAS) in supporting students’ mathematical problem-solving skills on linear equations in one variable (LEOV), systems of linear equations in two variables (SLETV), and combined linear equation problems. GEMAS was designed as a game-based learning medium that integrates mathematical tasks with problem-solving stages based on Krulik and Rudnick’s framework, namely read and think, explore and plan, select a strategy, locate and answer, and reflect and extend. This study employed a quantitative approach with a one-group pretest-posttest quasi-experimental design involving 60 students of SMPN 12 Sukabumi in the second semester of the 2024/2025 academic year. The instruments consisted of a mathematical problem-solving test and semi-structured interviews. Data were analyzed using paired-sample t-tests and normalized gain scores. The results showed statistically significant differences between students’ pretest and posttest scores across the three topics: LEOV, SLETV, and combined problems, with moderate normalized gain scores ranging from 0.3901 to 0.5465. These findings suggest that the use of GEMAS was associated with moderate improvement in students’ mathematical problem-solving skills. The study contributes to the development of mathematics educational games by aligning game-based activities with explicit problem-solving indicators, making GEMAS a potential learning medium to support the implementation of the Merdeka Curriculum.